ประสิทธิผลของการใช้แนวปฏิบัติทางคลินิกสำหรับป้องกันการเกิดแผลกดทับในผู้ป่วยสูงอายุโรคหลอดเลือดสมอง หอผู้ป่วยอายุรกรรมพิเศษ โรงพยาบาลแมคคอร์มิค - อิสรีย์ ขันชัยทิศ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Pressure ulcers have become a major and common complication among elderly patients who are hospitalized with stroke. This operational study aimed to evaluate the effectiveness of implementation of pressure sore prevention among elderly patients with stroke receiving treatment at the Private Medical Unit, McCormick Hospital, Chiang Mai. The research based on implementation model guidelines from the Registered Nurse Association of Ontario (RNAO, 2012). The subjects included 16 health care providers and 40 elderly patients. The research was conducted between May and August 2014. The first group of 20 patients did not receive pressure sore prevention guidelines while the remaining 20 patients did receive them. Study instruments included the Clinical Practice Guidelines Implementation for Pressure Sore Prevention in Elderly with Stroke, developed by Bunjongporn Kunphurk (2008), and consisted of 6 sections including 1) pressure sore risk assessment 2) skin care 3) position 4) pressure-redistributing devices 5) nutrition and 6) educational programs for health care personnel and elderly patients and their caregivers. Outcomes of Clinical Practice Guidelines (CPGs) implementation consist of incidence of pressure sore and caregiver and health care providers satisfaction with guideline implementation. Data were analyzed using descriptive statistics.